Perkembangan Asrama Al-Fathoniah Thailand Garut Dari Tahun 2012 - Sekarang - Sultan Muhamad Rizky (Priangan: Journal of Islamic Sundanese Culture, 2022)
The region of Southeast Asia is place with religious developments, particulary Islam scattered across Indonesia. However, ther is minority Muslim community in Thailand. In Southern Thailand the Muslim majority was in the Province of Pattani. Pattani was a colony of Thailand because it was intended to unite the country into one religion, one language, and one culture, Siam. Therefore, Pattani came to Indonesia to desive astrategy to rescue Pattani from the Thai government. Muslim Pattani came to Garut in Tarogong Kidul District, Village of Cibunar, Housing Jati Putra Asri teak after living in Bandung. On the 2014 collapse of Thailandâ€™s al-Fathoniyah Dorm, on account of many Pattani Muslims Living here. The Dorms have grown well until now.Â